Trauma-Induced Coagulopathy in Children - Lucisano, Amelia C.; Leeper, Christine M.; Gaines, Barbara A. (Seminars in Thrombosis and Hemostasis, 2020)
Trauma-induced coagulopathy (TIC) is well documented in injured children. However, many important features of pediatric hemostasis are still in development in early childhood and may impact TIC. Certain pediatric subgroups are at a higher risk. Traumatic brain injury, which occurs with a higher rate in children, and physical child abuse are known risk factors for TIC that deserve special consideration. Resuscitation of a pediatric trauma patient follows many of the same goals as in the injured adult trauma, although some key aspects of pediatric resuscitation require ongoing investigation. Venous thromboembolism occurs with higher rates in certain high-risk groups of pediatric trauma patients, although overall it is considerably less frequent in children as compared with adults.
Keywords: pediatric; hemostasis; trauma; coagulopathy; transfusion; thrombosis